A trivalent, inactivated influenza vaccine (Vaxigrip®): summary of almost 50 years of experience and more than 1.8 billion doses distributed in over 120 countries - Margaret Haugh; Viviane Gresset-Bourgeois; Bérengère Macabeo; Anne Woods; Sandrine I. Samson (Expert Review of Vaccines, 2017)
Introduction: Vaxigrip, a trivalent split-virion, inactivated vaccine available since 1968 has been in use longer than any other influenza vaccine. It is the most widely-used influenza vaccine, with more than 1.8 billion doses distributed in more than 120 countries. Areas covered: The significant body of evidence that confirms the efficacy, effectiveness, immunogenicity, and safety of Vaxigrip in healthy individuals of all ages and at-risk populations is summarized. The results from at least 15 randomized efficacy trials and 15 other studies have demonstrated that vaccination with Vaxigrip is efficacious against various clinical endpoints. It was estimated that more than 37 million laboratory-confirmed influenza episodes, 476,000 influenza-related hospitalizations, and 67,000 influenza-related deaths have been avoided by the more than 1.8 billion doses of Vaxigrip that have been distributed, emphasizing its important public health impact. Expert commentary: This strong evidence base in favor of Vaxigrip provides a robust foundation to support the implementation of the quadrivalent formulation. This quadrivalent formulation of Vaxigrip contains two A and two B influenza strains (VaxigripTetra), and has a similar immunogenicity and safety profile to the trivalent formulation while offering broader protection due to the addition of the second influenza B strain.